Efektivitas Tiga Bahan Aktif Insektisida Dalam Mengendalikan Hama Spodoptera frugiperda Pada Tanaman Jagung Manis (Zea mays L.) - Bersinar, Saras; Pramudi, Muhammad Indar; Liestiany, Elly (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
Corn in Indonesia is the second most important food crop after rice. There are many types or varieties of corn such as sweet corn and feed corn which are commonly used as food, feed, fuel, and industrial raw materials. The increasing productivity of corn as a food commodity is hampered by various factors, one of which is the presence of armyworm pests (Spodoptera frugiperda) which attacks the growing points of corn plants. ArmywormS. frugiperdais an invasive insect that has become a major pest of corn crops (Zea mays) in Indonesia. Severe crop losses caused by the damage caused by the attackS. frigiperdareaching 40%. Therefore, prevention is needed to control the armyworm pest, one of which is by using chemical insecticides that are relatively fast, time efficient and easy and produce satisfactory results. This study aims to observe symptoms of attack, calculate the intensity of damage, incidence of attack and percentage of damage to corn cobs. This study was conducted to analyze the effect of insecticide useEmamectin benzoate, lambda cyhalothrinAnd On Fipronwith different doses. This study used an experimental method with a Completely Randomized Design (CRD), namely water treatment (control) and 6 synthetic insecticide treatments, namelyEmamectin benzoate (KL1.1) 0.7 ml/L,(KL1.2) 1.2 ml/l,lambda cyhalothrin(KS2.1) 1 ml/L, (KS2.2)1.2 ml/l And On Fipron (KF3.1) 0,25 ml/L, (KF3.2) 1.2 ml/l. The results of this study indicate that insecticides with Kl treatment1.10.7ml/l can reduce the incidence of attacks by (19.17%), attack intensity by (0.7%) and cob damage (14.29%).